Hatchery field technicians in Tanzania change behavior after “social extension” mentorship program with Women in Business (WiB) mentors - Campbell, Zoë A.; Jumba, Humphrey (International Livestock Research Institute, 2025)
The Social Extension Mentorship Program was a pilot program supported by the PRomoting and Enabling Vaccination Efficiently, Now and Tomorrow (PREVENT) project. PREVENT was an initiative to increase hatchery vaccination for day-old chicks in mid-size hatcheries in Africa. Field Technicians, animal health technicians employed by private hatcheries, were part of the pathway to reach poultry producers with vaccinated chicks. In an early launch meeting of the PREVENT project, field technicians shared with ILRI gender researchers that they had sufficient technical training but rarely discussed or received training on the social skills required to deliver good extension, including gender dynamics. We proposed a pilot mentorship program in Tanzania, pairing five mentors with 12 mentees (Field Technicians linked to the PREVENT project) for five months of activities with the goal of supporting Field Technicians to deliver more inclusive, gender-responsive extension. The mentors were women agripreneurs who were supported and trained as young graduates using the Women in Business model to self-employ in chicken businesses. These businesses often involved selling inputs to poultry producers in their communities and buying back chickens and eggs, thereby providing them an income and giving their clients in rural areas access to better inputs and market prices for their products. The mentors had received coaching and guidance for their own businesses, had professional experience in the poultry value chain, and through a combination of personal experience and gender trainings, were able to articulate and guide the mentees to understand the gender dynamics in the poultry sector and how they could navigate them when delivering extension services. Project collaborators ILRI, GALVmed, and Ceva supported development of a pilot curriculum and trialing a mentor-mentee relationship for the purposes of improving future development programming. The Tanzania Livestock Research Institute (TALIRI) provided technical guidance to the curriculum. The objective was to develop learning objectives, curriculum, and format for the mentorship program with the goal of building the capacity for field technicians to deliver effective, gender-responsive extension services and qualitatively document lessons learned. Most of the mentees interviewed after the program were able to identify challenges unique to women in poultry production and some described changes in their extension, primarily targeting more household members when delivery extension, including women, young people, and household employees. The pilot was assessed through qualitative self-reflections of the mentees, which has limitations. We hope the pilot can be continued and more rigorously assessed in a future project.